Fenicios en el Atlántico. Excavaciones españolas en Lixus: los conjuntos "C Montalbán" y "Cata Basílica" - López Roa, Carmen; Escacena Carrasco, José Luis; Rodero, Alicia (Complutum, 1996)
Sin resumen